2014
DOI: 10.1111/ijn.12315
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory focus and burnout in nurses: The mediating effect of perception of transformational leadership

Abstract: This correlation study investigated the relationship between nurses' regulatory focus and burnout, as mediated by their perceptions of transformational leadership, using a cross-sectional research design with anonymous questionnaires. In July-August 2012, data were collected from 378 nurses from three hospitals in Shaanxi Province, China, using self-report questionnaires for measuring the nurses' regulatory focus, their level of burnout and their perception of whether the leadership of their supervisor was tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
4
19
0
Order By: Relevance
“…Ten studies examined the association between organisational context and nurse burnout (Guo et al., 2016; Liu et al., 2018, 2019; Lu et al., 2015; Meng, Jin, & Guo, 2016; Shao et al., 2018; Shi et al., 2015; Yu, Jiang, & Shen, 2016; Zhang et al., 2014; Zhou et al., 2015). Six reported that the average prevalence of high burnout was 42.79% (range, 34.9%–57.1%) (Guo et al., 2016; Liu et al., 2018, 2019; Lu et al., 2015; Zhang et al., 2014; Zhou et al., 2015), which was similar to U.S. hospital nurses (Aiken et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies examined the association between organisational context and nurse burnout (Guo et al., 2016; Liu et al., 2018, 2019; Lu et al., 2015; Meng, Jin, & Guo, 2016; Shao et al., 2018; Shi et al., 2015; Yu, Jiang, & Shen, 2016; Zhang et al., 2014; Zhou et al., 2015). Six reported that the average prevalence of high burnout was 42.79% (range, 34.9%–57.1%) (Guo et al., 2016; Liu et al., 2018, 2019; Lu et al., 2015; Zhang et al., 2014; Zhou et al., 2015), which was similar to U.S. hospital nurses (Aiken et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Other factors related to organisational context have been shown to influence patient and nurse outcomes, for example, the value fit between nurses and hospitals, structural empowerment, transformational leadership and patient–nurse ratios (Guo et al., 2016; Shao et al., 2018; Shi, Zhang, Xu, Liu, & Miao, 2015). Additionally, findings from qualitative studies (Tao, Ellenbecker, Wang, & Li, 2015; Zhu, Rodgers, & Melia, 2014) have provided insight about what influences organisational context such as a blame culture, inadequate nursing staff and a lack of risk management.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the results showed that transformational leadership has a positive impact on nurses' safety performance [13]. Also, this type of leadership style was positively related to staff nurse job satisfaction [14] and lead to diminished burnout [15]. Moreover, there are conflicting findings about the relationship between transformational leader-ship and staff commitment to patients and their organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The result is a defensive spiral, with fear of punishment producing preventive and avoidance strategies. Little surprise that this is linked with stress and burnout, with patients' poor experiences translating into damaging work environments for nurses and with knock‐on effects into the care delivered. Safety, then, becomes something we only notice in its absence, and preoccupation with things that go wrong means that good practice, even excellent practice, passes unremarked.…”
mentioning
confidence: 99%
“…Things go right almost all the time; by understanding this and how we achieve this in the complex, dynamic and highly charged healthcare environment, we can learn what we need to promote in order to grow this. For example, perceiving transformational characteristics amongst leaders is linked with staff reporting ‘organizational citizenship behaviour, innovative performance, work engagement, job satisfaction and affective organizational commitment’, all characteristics likely to accompany greater nurse–patient engagement. When nurses spend more time with their patients, adverse events may be less likely, as lack of contact time with patients is blamed .…”
mentioning
confidence: 99%